PENGARUH LANGSUNG DAN TIDAK LANGSUNG DARI KEWAJARAN HARGA, KUALITAS MAKANAN, DAN PEMASARAN DARI MULUT KE MULUT TERHADAP NIAT PEMBELIAN: PERAN CITRA MEREK (STUDI KASUS MIXUE) - Putri, Safir Dzakiyyah Aziziyah (APPS Publications, 2023)
Purchase intention holds significant importance in understanding factors that drive customers’ decision-making processes and subsequent purchasing behavior, using Mixue as a case study, this study focuses on the purchase intention of Mixue by exploring determinants such price fairness, food quality and word-of-mouth and the indirect effect of brand image. The study was conducted in Jakarta with a total of 206 samples which were analyzed using the Smart-PLS software. The results indicated that food quality and word-of-mouth have a positive significant influence on purchase intention and that price fairness does not. Additionally, the relationship between the determinants is mediated by brand image. This study contributes to the existing literature on purchase intention by providing empirical evidence on Mixue and emphasizes the importance of enhancing food quality, fostering positive word-of-mouth recommendations, and strengthening brand image in hopes of providing valuable insights for Mixue management for developing effective marketing strategies.